2022
DOI: 10.1039/d2ra02450k
|View full text |Cite
|
Sign up to set email alerts
|

Uracil derivatives as HIV-1 capsid protein inhibitors: design, in silico, in vitro and cytotoxicity studies

Abstract: The paper describes the design, synthesis, computational and biological validation of a series of novel uracil derivatives as effective HIV capsid protein inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Sakakibara et al [72] The synthesised compounds were tested for its anti-HIV-1 activity. [73] The results have shown that compound 6-amino-3-(3,5-dimethylbenzyl)-1-(4-aminobenzyl)uracil 140 a exhibited significant activity against HIV-1 with an EC 50 value of 0.01 μM respectively.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sakakibara et al [72] The synthesised compounds were tested for its anti-HIV-1 activity. [73] The results have shown that compound 6-amino-3-(3,5-dimethylbenzyl)-1-(4-aminobenzyl)uracil 140 a exhibited significant activity against HIV-1 with an EC 50 value of 0.01 μM respectively.…”
Section: Introductionmentioning
confidence: 95%
“…The reaction involved the treatment of 6‐azido‐1‐(4‐nitrobenzyl) uracil 139 a and 6‐azido‐1‐(2‐nitrobenzyl)uracil 139 b derivatives using NaBH 4 in the presence of methanol and THF to yield diamino derivatives of type 140 a – b . The synthesised compounds were tested for its anti‐HIV‐1 activity [73] . The results have shown that compound 6‐amino‐3‐(3,5‐dimethylbenzyl)‐1‐(4‐aminobenzyl)uracil 140 a exhibited significant activity against HIV‐1 with an EC 50 value of 0.01 μM respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 As an anti-neoplastic agent, uracil itself has been used in combination with tegafur (a chemotherapeutic prodrug of 5-fluorouracil) to treat various cancers, including breast, prostate, and liver cancer. 7 Very recently, Ramesh et al 8 synthesized a series of bis-uracil substituted aryl methylene derivatives. In vitro study of the synthesized compounds in HIV p24 assay revealed that five compounds, shown in Figure 5, possess promising HIV-1 capsid protein inhibitory efficacy.…”
Section: Introductionmentioning
confidence: 99%